Respostas
respondido por:
0
Resposta:
f(x) = 2x² - 3x +1
f(√2/3) = 2.(√2/3)² - 3(√2/3) + 1
f(√2/3) = 2.(2/9) - √2 + 1
f(√2/3) = 4/9 - √2 + 1
f(√2/3) = 13/9 - √2
f(√2/3) = 1,444... - 1,414213...
f(√2/3) = 0,030231
respondido por:
1
Resposta:
O resultado da expressão é 411.
Explicação passo-a-passo:
fx = 1
21² - 31 + 1
441 - 31 + 1 21 x 21 = 441 441
410 + 1 = - 31
411 410
Espero ter ajudado :)
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás